2020
DOI: 10.1002/ccd.28957
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aortic angle on transcatheter aortic valve implantation outcome with Evolut‐R, Portico, and Acurate‐NEO

Abstract: Objectives: To investigate paravalvular leak (PVL) and devices success rates according to aortic angle (AA) in patients undergoing transcatheter aortic valve implantation (TAVI) with three new-generation self-expanding devices. Background: The impact of aortic angle (AA) on TAVI device success and PVL rates is controversial. Methods: This retrospective study included 392 patients submitted to TAVI for severe aortic stenosis with Portico, Evolut-R and Acurate-NEO, and available AA measurements at computed tomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 17 publications
(32 reference statements)
1
38
1
Order By: Relevance
“…The geometric specialty of the Evolut R is a highest radial force at the LVOT edge of the prosthesis and a continuously decreasing diameter towards the stent center. With respect to this, a recently published study identified the implantation depth as predictor for moderate or severe PVL [15]. Our data showed no influence of the implantation depth or the eccentricity of the annular plane (native or the prosthesis on this height) on PVL.…”
Section: Paravalvular Leakagesupporting
confidence: 48%
“…The geometric specialty of the Evolut R is a highest radial force at the LVOT edge of the prosthesis and a continuously decreasing diameter towards the stent center. With respect to this, a recently published study identified the implantation depth as predictor for moderate or severe PVL [15]. Our data showed no influence of the implantation depth or the eccentricity of the annular plane (native or the prosthesis on this height) on PVL.…”
Section: Paravalvular Leakagesupporting
confidence: 48%
“…Notably, first-generation prostheses were used in most patients. According to the existing knowledge, although some studies have pointed out the association between increased angulation and worse clinical outcomes in Evolut R and Pro, 11,16,21 studies have also indicated that next-generation self-expanding valves might reduce the adverse impact of an increased AA. 10,11,15,22,23 Recently, the fourth-generation device Evolut FX, with improved delivery system flexibility, has just been approved by the Food and Drug Administration.…”
Section: Discussionmentioning
confidence: 99%
“…An extremely horizontal aorta was defined as an aortic root angle ≥70° between the horizontal plane and the aortic annulus (Figure 1). 10,11 Valve calcification severity was classified into four grades (none, mild, moderate, and severe) as previously described 12 . The aortic valve type was identified by two experienced cardiologists according to Sievers' classification 13 .…”
Section: Methodsmentioning
confidence: 99%
“…All events, including procedural and device success, were classified according to the Valve Academic Research Consostium‐2 (VARC‐2) criteria 8 . Horizontal aorta was defined as an aortic angle >57° 9 …”
Section: Methodsmentioning
confidence: 99%
“…Coronary artery overlap was deemed severe if a neocommissure and coronary orifice were 0 to 20 apart as reported by other Authors. 6 According to measurements proposed by Fuchs et al 9 THV commissural alignment was defined as: (1) aligned (angle deviation 0 to 15 );…”
Section: Endpoints and Definitionmentioning
confidence: 99%